2021
DOI: 10.1002/jmv.27002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia in patients following their recovery from severe coronavirus disease 2019

Abstract: Coronavirus disease 2019 (COVID-19) is caused by a contagious virus that has spread to more than 200 countries, territories, and regions. Thousands of studies to date have examined all aspects of this disease, yet little is known about the postrecovery status of patients, especially in the long term. Here, we examined erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and serum albumin biomarkers in patients with a history of severe and mild-to-moderate COVID-19 following their recovery. In patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
(86 reference statements)
1
20
0
Order By: Relevance
“…Both demonstrated that a reduction of SA concentration could be a predictor for death or progression in COVID-19 patients with hypoalbuminemia [ 21 , 22 ], whereas other studies observed that the normalization of SA may be also associated with a good prognosis [ 23 ]. Ali et al demonstrated that hypoalbuminemia may persist post recovery in patients with a history of severe COVID-19 [ 24 ]. These studies confirm the prognostic role on SA in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Both demonstrated that a reduction of SA concentration could be a predictor for death or progression in COVID-19 patients with hypoalbuminemia [ 21 , 22 ], whereas other studies observed that the normalization of SA may be also associated with a good prognosis [ 23 ]. Ali et al demonstrated that hypoalbuminemia may persist post recovery in patients with a history of severe COVID-19 [ 24 ]. These studies confirm the prognostic role on SA in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…When the two target genes (ORF1ab and E) tested positive by specific real-time RT-PCR, a cycle threshold value (Ctvalue) ≤ 36.7 was defined as a positive result and a Ctvalue of greater than 36.7 was defined as a negative result. 16,17 Ct-value is a semi-quantitative assessment that can widely show the concentration of viral genetic material in the patient samples following testing by RT-PCR. A low Ct-value indicates a high concentration of viral genetic material, which is typically associated with a high risk of severity, but a high Ct-value indicates a low concentration of viral genetic material which is typically associated with a lower risk of the disease severity.…”
Section: Reverse-transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…Some of the Federal Drug Administration (FDA) approved drugs acting as the inhibitor of the coagulation factor Xa are apixaban (clinical trial: NCT03907046), dabigatran (Pradaxa®), and rivaroxaban (Xarelto®) ( Chen et al, 2020 ). Because persistently high levels of inflammatory biomarkers in the blood have been detected in the recovery stage of COVID patients ( Ali et al, 2021 ), it will be important to determine whether such chronic inflammations can induce stress granule formation in the brain, as it often does under other stress response conditions ( Herman et al, 2019 ). Statins, minocycline, and melatonin are the most commonly administered anti-inflammatory drugs used to treat the neuroinflammation in the CNS ( Kaelber et al, 2016 ).…”
Section: Summary and Future Directionsmentioning
confidence: 99%